The Case for Roughly Stabilizing the Real Value of the Dollar - Williamson, John (American Economic Review, 1989)
The title of my paper implies the following five claims: 1) It is possible for macroeconomic policy to influence exchange rates in a substantive way; 2) It is desirable that macroeconomic policy target the exchange rate; 3) It is nevertheless desirable to leave substantial latitude for exchange rates to fluctuate around their target levels; 4) The target should be a real rather than nominal exchange rate; 5) The real value of the dollar was broadly appropriate when this paper was written (December 1988). The paper is devoted to explaining the basis for these five propositions.